KONSERVASI BANGUNAN BERSEJARAH RUMAH “SIWALUH JABU” DESA LINGGA - Erwin Ardianto Halim (Serat Rupa: Journal of Design, 2020)
Traditional house is an authentic historical and cultural heritage architecture and is full of philosophy. One of them is Karo Traditional House which is usually called Siwaluh Jabu because it is inhabited by eight family heads. The modernization process that is developing rapidly in Indonesia has led to significant changes. This research was conducted by taking data and interviewing directly on the location of the Siwaluh Jabu Traditional House and then analyzing the form of shift that will be sought for handling solutions in conserving the interior of the Siwaluh Jabu Traditional House where conservation has the aim of preserving while still paying attention to and maintaining cultural on it.